2008
DOI: 10.1007/s00484-008-0156-5
|View full text |Cite
|
Sign up to set email alerts
|

Regional trends for bud burst and flowering of woody plants in Norway as related to climate change

Abstract: Data series for bud burst, beginning of flowering and petal fall for 20 species of deciduous trees and conifers at four sites in different regions of southern Norway have been analysed and related to temperature series. On average, the spring phenophases occurred 7 days earlier during the period 1971-2005. The most significant linear trends were observed for the earliest phases. The trends in this period were compared with trends in other periods, the longest one starting in 1927. Those starting in cold decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 35 publications
4
53
0
1
Order By: Relevance
“…It is well known [9,[12][13][14][15][16][17] that spring temperature is the dominating factor for explaining the onset of the growing season in Fennoscandia. However, very few high resolution gridded temperature datasets covering the whole area exist, and the meteorological stations are relatively sparse and unevenly distributed within Fennoscandia.…”
Section: E-obs Temperature Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known [9,[12][13][14][15][16][17] that spring temperature is the dominating factor for explaining the onset of the growing season in Fennoscandia. However, very few high resolution gridded temperature datasets covering the whole area exist, and the meteorological stations are relatively sparse and unevenly distributed within Fennoscandia.…”
Section: E-obs Temperature Datamentioning
confidence: 99%
“…Karlsen et al [10], Xu et al [1] and Bi et al [11] have also observed the same pattern in Northern Europe as elsewhere in the northern lands (>50°N ), but found a lesser increase of the length of the growing season (photosynthetic active period) in the northern parts of Fennoscandia compared with the southern parts of the same area. It is well known [9,[12][13][14][15][16][17] that the spring temperature is the dominating factor for explaining the onset of the growing season in Fennoscandia. Xu et al [1] also showed that the onset of the growing season was significantly correlated with the spring temperatures in the circumpolar and circumboreal areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, Pudas et al (2008a,b) report that this shortening trend seems to have ended, with an earlier onset of spring and no changes in the timing of autumn phenophases for northern Finland for the [1997][1998][1999][2000][2001][2002][2003][2004][2005][2006] period. In central, southern, and western oceanic parts of Fennoscandia, there are indications of a different pattern, with only weak trends in change of onset and end of the growing season on a century time scale, but with significant earlier onset of spring phenophases during the last 2 decades (Emberlin et al 2002, Nordli et al 2008, Pudas et al 2008b). However, neither the spatial nor the temporal pattern of the changes in the growing season within Fennoscandia is obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Menzel & Fabian 1999, Menzel et al 2001, Peñuelas et al 2002, Nordli et al 2008. Most of these studies are based on phenological observations and temperature measurements starting in the 1950s and 1960s.…”
Section: Introductionmentioning
confidence: 99%